A produção de porongos/cuias como uma estratégia para a reprodução social da agricultura familiar no distrito de Arroio do Só, município de Santa Maria - RS - Cancelier, Janete Webler (2018)
This research presents reflections about the production of gourds and its importance as an activity that allows economic and social development of family farming, specifically at Arroio do Só District, City of Santa Maria (RS). The objective of this research was to recognize and identify the role of family farmers and family agroindustry who produce and process gourds, as well as the different productive process that make up this productive chain. For the accomplishment of the investigation, it was used bibliographic research, in which theoretical references related to the subject were addressed, and also field research, with the application of structured interviews and forms, direct observation with field journaling, in order to understand the phenomenon in its singularities and totalities. There was also a search for qualified information provided by the gourds producers and the agroindustry workers. This approach allowed the perception of the different realities lived by the family farmers and the agroindustry workers; the strategies that are used; the different phases of the production process; the traditional and artisanal character of the activity; and the many accessed spaces of commercialization, in both intern and extern market. The producers of gourds resist through the passage of years facing all kinds of difficulties, since they still suffer from invisibilization by the public power. In this way, the economic relevance that the activity has to the population involved in the production process is revealed, since this people get little or none support from municipal or state institutions. The production of gourds and the insertion of family agroindustry at Arroio do Só District enable a new socioeconomic dynamic, contributing to the permanency of people at the countryside because of the demand of work and income generation.